2017
DOI: 10.1097/md.0000000000007212
|View full text |Cite
|
Sign up to set email alerts
|

Propofol decreases etomidate-related myoclonus in gastroscopy

Abstract: Objective:Myoclonus, a common complication during intravenous induction with etomidate, is bothersome to both anesthesiologists and patients. This study explored the preventive effect of pretreatment with propofol on etomidate-related myoclonus.Methods:This was a prospective, double-blind, clinical, randomized controlled study. Totally, 363 patients who were scheduled for a short-duration, painless gastrointestinal endoscopy were divided into 5 groups. Four groups received 0 mg/kg (E group), 0.25 mg/kg (LPE gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…[32,33,39,44] Five RCTs compared propofol plus etomidate with etomidate or propofol alone. [34–36,38,41] Three RCTs compared propofol plus etomidate with propofol alone. [27,37,43] The remaining 2 trials compared propofol plus etomidate with etomidate alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32,33,39,44] Five RCTs compared propofol plus etomidate with etomidate or propofol alone. [34–36,38,41] Three RCTs compared propofol plus etomidate with propofol alone. [27,37,43] The remaining 2 trials compared propofol plus etomidate with etomidate alone.…”
Section: Resultsmentioning
confidence: 99%
“…One used a random digital method involving the use of computers, [27] 1 used computer generated random numbers table [7] , 4 RCTs used a random number table. [32,36,38,39] One RCT did not mention whether a random was used. [44] The rest did not provide any detailed information.…”
Section: Resultsmentioning
confidence: 99%
“…Etomidate may also play a pre-administration role with propofol in the admixture. [ 15 ] Although the overall hypoxemia probability of the PE 1 group is lower than that of the other 2 groups, the probability of severe hypoxemia is higher. It may be that the depth of anesthesia is shallower than that of the other 2 groups, and the patient has a choking reaction that causes severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of etomidate induced myoclonus is still not clear, several studies suggest that it may represent a type of seizure. [12] However, some cases are also reported which showed that etomidate has caused generalized tonic clonic seizures. [313233] In this study, we made an attempt to quantify the myoclonus biochemically by measuring CPK levels before and after giving etomidate and calculating the difference in CPK levels.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of drugs, including neuromuscular blocking agents,[78] opioids,[9] dexmedetomidine,[510] midazolam,[611] propofol,[12] ketamine,[13] gabapentin,[14] and magnesium sulphate[1115] have been investigated for their ability to suppress these myoclonic movements. These drugs are; however, associated with side effects such as excessive sedation, delayed recovery, and respiratory inhibition.…”
Section: Introductionmentioning
confidence: 99%